Preparation and characterisation of active component in nabeez water of ajwa dates (Phoenix dactylifera L.) mixed in healthy brown rice milk (BRM) as halal beverage - Rais Nur Latifah; Sri Rahmania (Jurnal Litbang Industri, 2022)
Nabeez water or dates infused water is the Prophet Muhammad’s favourite drinks. Flavonoids, phenols, alkaloids, and beta D-glucan in dates have anticancer and antitumor activity. This study aims to prepare and characterise the active component of nabeez water made with ajwa dates, applied in BRM (Brown Rice Milk) products. BRM is an innovative plant-based beverage made with brown rice and nabeez water from ajwa dates as a halal beverage for immune booster in the era of the covid-19 pandemic. The methods to analysis the products are the preparation of nabeez water, the pasteurisation method for halal drinks with the LTLT (Low-Temperature Long Time) method, toxicity testing, pyrochemical testing, functional group analysis using FTIR instrument, milk dye degradation analysis and stability test. The results showed phenolic, flavonoids, catechol tannins, saponins, alkaloids, Mayer's test, and Wagner's test in halal drinks but not shown the tannin of gallate, anthraquinone, steroid test, and triterpenoid test. The toxicity test using the Brine Shrimp Lethality Test (BSLT) method of the LC50 value showed the Concentration 50 (LC50) value is 721.56 ppm. Analysis of functional groups using FTIR showed absorption of functional groups such as OH (hydroxide), C=O, C=C, C=CH, and Ar-H.